2018
DOI: 10.21608/jades.2018.62430
|View full text |Cite
|
Sign up to set email alerts
|

Field studies on the protozoan distribution in Damietta and Rosetta branches of the River Nile, Egypt

Abstract: This study was carried out during a period extending between February 2016 and January 2017 in both Damietta and Rosetta branches of the Nile. Water samples were collected at eight sampling sites; four at Damietta and the others at Rosetta branch so as to detect the variability of the protozoan organisms and evaluate some physico-chemical parameters. It was proved that the protozoan genera of Rosetta branch showed more diverse as compared with those of Damietta one ( 46 and 35 genera respectively). These organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The free-living planktonic Protozoa community in this freshwater study area was represented by 54 species (Table 4 ), a value well within the range found in most lotic environments of 20–200 species 14 . The species identified belonged to 45 genera that were more diversified than reported for other regions along the Damietta branch (e.g., Qalyubia and Daqahlia, 35 genera recorded) but similar to that of the Menofia region on the Nile's Rosetta branch with 45 genera 20 . The Damietta protozoan community consisted of six main phyla: Amoebozoa (10 species), Choanozoa (4 species), Heliozoa (4 species), Cercozoa (5 species), Myzozoa (1 species), and Ciliophora (30 species).…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The free-living planktonic Protozoa community in this freshwater study area was represented by 54 species (Table 4 ), a value well within the range found in most lotic environments of 20–200 species 14 . The species identified belonged to 45 genera that were more diversified than reported for other regions along the Damietta branch (e.g., Qalyubia and Daqahlia, 35 genera recorded) but similar to that of the Menofia region on the Nile's Rosetta branch with 45 genera 20 . The Damietta protozoan community consisted of six main phyla: Amoebozoa (10 species), Choanozoa (4 species), Heliozoa (4 species), Cercozoa (5 species), Myzozoa (1 species), and Ciliophora (30 species).…”
Section: Resultsmentioning
confidence: 54%
“…Therefore, accurately identifying the Protozoa species associated with the environmental factors is necessary to conduct a meaningful ecological study. Although many studies have examined planktonic Protozoa community's distribution, composition, and dynamics and their role as biological indicators in lotic systems, few have been conducted within the Nile River 18 , 20 , 21 . No studies have been conducted specifically on planktonic Protozoa in the Damietta region.…”
Section: Introductionmentioning
confidence: 99%
“…Galal and Nabet ( 2017 ) studied the protozoan fauna in 3 aquatic freshwater sources in El-Menoufeyia Province and recorded sarcodines belonging to the genera Amoeba , Arcella , and Nuclearia . Despite extensive studies made by Galal ( 2018 ) on the protozoan fauna of surface water from Rosetta and Damietta branches of the River Nile, Vannella species were not detected in these localities. Fishar et al ( 2019 ) studied the community composition of zooplankton in El-Rayah El-Behery, Egypt, and recorded nine protozoans with no names except Vorticella .…”
Section: Discussionmentioning
confidence: 89%
“…Comparing the present data with those of Damietta branch of the Nile ( Galal, 1999), it was proved that pH, DO, NO 3 , PO 4 values are mostly higher in the latter branch except those of the summer season in case of the first two parameters (pH and DO), while those of NH 3 and OM showed an antagonistic behavior. The physicochemical parameters of Rosetta branch of the Nile (Galal et al, 2008;Galal, 2018)) are more or less higher than those of Damietta (Galal, 2009), but still less than those of Lake Manzala. This comparison indicated that the pollution level belonging to these three water bodies are different; those of the Nile branches were less polluted than Lake Manzala which could be referred to extensive illegal discharges of the various pollutants from more than five provinces as mentioned earlier in the latter water body (Lake Manzala).…”
Section: Resultsmentioning
confidence: 94%